Nonlinear iterative methods for solving the split common null point problem in Banach spaces - Suthep Suantai (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group In this work, we study the split common null point problem in the framework of Banach spaces. We propose an iterative scheme for solving the problem and then prove strong convergence theorem of the sequences generated by our iterative scheme under suitable conditions. We finally provide some numerical examples to support the main theorem.